2018
DOI: 10.1002/joc.5532
|View full text |Cite
|
Sign up to set email alerts
|

Extreme drought hotspot analysis for adaptation to a changing climate: Assessment of applicability to the five major river basins of the Korean Peninsula

Abstract: This study proposes a quantitative approach for extreme drought hotspot assessment related to climate change, the hotspot drought risk index (HDRI), and evaluates the response of extreme drought to climate change in the five major river basins of the Korean Peninsula. According to an analysis of seasonal and regional drought characteristics on the Korean Peninsula, drought occurs most frequently in spring, and the central and southern areas are generally more vulnerable to drought. Drought risk analysis under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Various drought indices related to agricultural, soil moisture and streamflow data are used to quantify the climate dryness anomalies. For example, Standardized Precipitation Index (SPI) and Palmer Hydrological Drought Index (PHSI) have been used in practice to quantitatively analyze the characteristics of meteorological and hydrological droughts [7,8]. A threshold level method is another frequently applied tool for defining a drought event and has practical advantages-(i) no a-priori knowledge of probability distributions is required and (ii) it simply and directly produces drought characteristics such as duration and severity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Various drought indices related to agricultural, soil moisture and streamflow data are used to quantify the climate dryness anomalies. For example, Standardized Precipitation Index (SPI) and Palmer Hydrological Drought Index (PHSI) have been used in practice to quantitatively analyze the characteristics of meteorological and hydrological droughts [7,8]. A threshold level method is another frequently applied tool for defining a drought event and has practical advantages-(i) no a-priori knowledge of probability distributions is required and (ii) it simply and directly produces drought characteristics such as duration and severity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…According to IPCC (2012) at a medium level of confidence, drought is likely to increase in future where some region may experience more intense drought. Several regional studies performed on various parts of the world (Wang et al, 2011;Yu et al, 2014;Nam et al, 2015;Chen and Sun, 2017;Thilakarathne and Sridhar, 2017;Lee et al, 2018;Spinoni et al, 2018) invariably reported the increase in the drought events in changing climatic conditions. During 1950-2006, Wang et al (2011 observed that soil moisture droughts became longer, more severe and more frequent for central and northeastern China.…”
Section: Introductionmentioning
confidence: 99%
“…Nam et al (2015) analysed the future drought characteristics over South Korea using SPEI, Standardized Precipitation Index (SPI), and Self-Calibrating Palmer Drought Severity Index (SC-PDSI); they reported an increasing drought severity and magnitude in the region. Majority of Korean Peninsula is also found to experience significant drought risk under various climatic scenarios (Lee et al, 2018). Spinoni et al (2018) analysed the drought over Europe under RCP 4.5 and RCP 8.5 scenario using SPI, SPEI, and Reconnaissance Drought Indicator (RDI).…”
Section: Introductionmentioning
confidence: 99%
“…Droughts are expected to become more catastrophic as climate forecasts indicate that droughts will become more intense in many areas (Downing 1993;IPCC 2012). Also, various regional studies (Chen and Sun 2017;Kumar et al 2013;Lee et al 2018;Nam et al 2015;Spinoni et al 2018;Thilakarathne and Sridhar 2017) conducted in several regions of the world have consistently indicated an increase in drought occurrences as climatic conditions change.…”
Section: Introductionmentioning
confidence: 97%